The Effectiveness of Exclusive Breastfeeding in Preventing Stunting Among Children Under Five: A Systematic Literature Review: Literature Review : Effectiveness of Exclusive Breastfeeding with Stunting Incidence in Toddlers - Suciati, Mohammad Irwansyah; Munir, Zainal (Caring : Jurnal Keperawatan, 2024)
Stunting is caused by the problem of lack of nutrition for a long time due to feeding to meet the growth and development needs of toddlers who are not exclusively breastfed for 6 months from the first birth so that their nutrition is not fulfilled. The purpose of this study was to determine the effectiveness of exclusive breastfeeding with the incidence of stunting in toddlers. The research method we use here is a literature review using electronic databases through international and national journals such as Google Scholar, Science Direct, and Pro-Quest, with the keywords exclusive breastfeeding and stunting in toddlers. An initial literature search found 33 articles (Google Scholar 14, Portal Garuda 8, Science Direct 6, Pro-Quest 5,). The 14 articles issued were out of sync with the topic of discussion, namely the effectiveness of exclusive breastfeeding with the incidence of stunting in toddlers and 19 full text articles that met the criteria. Conclusion : Exclusive breastfeeding is an effective way to prevent stunting in toddlers. This method can significantly prevent stunting so that exclusive breastfeeding for toddlers for the first 6 months after birth can help toddlers grow and develop.